(Not for Issued) Battle for the Mind : A Physiology of Conversion and Brain-Washing - Sargant, William (London Heinemann, 1957)
An attempt to explain "conversion", political and religious, in terms of Pavlovian psychology
Include Illustration and Index
Keywords: Brainwashing -- Conversion--Psychology